ANALISIS KESESUAIAN LAHAN DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) BULUH CINA, RIAU - Ikhsani, Hanifah; azwin, Azwin; Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Forest Area with Special Purposes (KHDTK) Buluh Cina requires a land suitability analysis so that the development of plant species can be carried out optimally. This study aims to map land units and determine land suitability classes. This study uses aerial photography to classify land cover and take soil samples. Furthermore, overlay analysis and species matching were carried out for 7 types of plants including durian, rambutan, sengon, mango, cacao, pineapple, and corn. The land suitability class is divided into 4 levels namely, very suitable (S1), suitable (S2), marginally suitable (S3), and not suitable (N). Based on the results, the actual land suitability class at KHDTK Buluh Cina class S1 was rambutan at SPL I and III. Land suitability class S2 is rambutan at SPL II and IV. S3 land suitability classes are durian, sengon, mango, cocoa, pineapple, and corn in SPL I, II, III, and IV. The potential land suitability class at KHDTK Buluh Cina class S1 is rambutan at SPL I, II, III and IV. Land suitability class S2 is durian, sengon, and cocoa at SPL I, II, III, and IV. S3 land suitability class is mango, pineapple, and corn in SPL I, II, III, and IV.